EXPLORING NON-NATIVE ENGLISH TEACHERS’ ORAL CORRECTIVE FEEDBACK IN CLASSROOM - Ai Rachma Yunita; Ateng Kurnia; Wahid Hasyim (English Education and Applied Linguistics Journal (EEAL Journal), 2020)
This study aims to describe the types of oral corrective feedback used by teacher in classroom activity. To achieve the aim, the study used descriptive qualitative design in order to answer the research problem; what are types of oral corrective feedback used by teacher in the classroom activity. The data were collected from three non-native English teachers through observation by taking audio/videos of the teaching and learning process. The videos were transcribed and then analyzed it for gaining the result. This study employs six types of teachers’ feedback by Ellis (2009) as checklist criteria. By doing so, they are able to strengthen the findings into the assessment of language teachers education. The result shows that teacher A used explicit correction and repetition in her classroom activity. Teacher B used clarification request. Teacher C used clarification request and explicit correction. In conclusion, the dominant types on teachers’ oral CF used in the classroom activity is clarification request. However, teachers’ strategy on give the corrections toward students’ erroneous in classroom activity is different depend on the mistakes and the conditions of the students itself.